Feeding and Natural Incubation Practices of IndigenousChickens in Kannur and Kozhikode Districts of Kerala, India - Girish Kumar, P; Richard Churchil, R (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A survey was conducted among native chicken farming households in Kannur (n=21) and Kozhikode (n=43) districts of Kerala, India, to document feeding and natural incubation practices. The findings revealed that 47.62% of farmers in Kannur and 30.23% in Kozhikode did not provide supplementary feed, while others mainly offered paddy or rice for nutritional and behavioural purposes. Feeding was typically practiced at noon or evening, with most Kannur farmers providing less than 10 g per bird per day, compared to 10–20 g in Kozhikode. Drinking water was not provided by 47.62% of Kannur farmers and 39.53% of Kozhikode farmers, whereas the others used well water served in coconut shells or steel utensils. Plastic cans and rubber baskets filled with sand were the common nest box choices. Farmers generally incubated 9–12 eggs per broody hen, achieving hatchability rates exceeding 60%. Overall, the study highlights that indigenous chickens require minimal care for feeding and watering due to their scavenging ability, while natural incubation practices ensure satisfactory hatchability across both districts.